STEM in the EAR - Johnson, Ann (Journal of the early Republic, 2016)
Situate science and STEM in the early republic, doing so can be challenging. What our historical subjects meant by words like “science” and “medicine” can be profoundly different from their use in the twenty-first century. Several phenomena of the early republic engage science in important and interesting ways, and overlooking science results in a skewed account. Ubiquity, as much as its poor resemblance to post-WWII science, helps account for both its invisibility and importance in the historiography of early America. A renewed attention to the roles of science, technology, engineering, and mathematics in the early republic will enrich the classic questions of the period, offering new insights about political formation and commercial development. A key consideration is not to ask “what was science?” but rather to ask “what counted as science?” Why did a particular activity or body of knowledge count as science, and what was at stake in making a claim of being scientific?